Status of Contamination and Distribution of Effluents in Tasik Chini, Pahang, Malaysia - Islam, Mir Sujaul; Arafat, Md. Yasir; Zularisam, A. W.; Mohamad Idris, Ali (National Institute of Ecology, 2016)
The study investigates the spatial variation and index of water quality in Tasik Chini (Chini Lake), Pahang, Malaysia. Water sampling was taken from 12 representative sites within the lake and two major feeder rivers. Physico-chemical parameters and heavy meter concentrations were analyzed using standard procedures. Observed data were calculated according to Department of Environment Water Quality Index (DOE-WQI) and classified to compare with National Water Quality Standard, Malaysia (NWQS). TSS, TDS and nitrate was categorized under class I. Water temperature, DO, BOD and turbidity was categorized under class II. Among other, pH, ammonical nitrogen (AN) and COD was under class III. Study revealed that station T2 was worse in condition followed by station T1 and L7. Heavy metals estimated by ICPMS indicated that Fe and Mn concentration were nigh in the mining zone station T2, whereas, sites L4 and L8 had the highest concentration of Ba and Pb. The lake water quality was classified as class II based on WQI Malaysia. That is quite suitable for body contact and recreational purpose. In general, water quality of Tasik Chini varied over space of the catchment and most affected indicators were AN, COD and pH.